Abscisic Acid-Induced Stomatal Closure: An Important Component of Plant Defense Against Abiotic and Biotic Stress - Bharath, Pulimamidi; Gahir, Shashibhushan; Raghavendra, Agepati S. (Frontiers in Plant Science, 2021)
Abscisic acid (ABA) is a stress hormone that accumulates under different abiotic and biotic stresses. A typical effect of ABA on leaves is to reduce transpirational water loss by closing stomata and parallelly defend against microbes by restricting their entry through stomatal pores. ABA can also promote the accumulation of polyamines, sphingolipids, and even proline. Stomatal closure by compounds other than ABA also helps plant defense against both abiotic and biotic stress factors. Further, ABA can interact with other hormones, such as methyl jasmonate (MJ) and salicylic acid (SA). Such cross-talk can be an additional factor in plant adaptations against environmental stresses and microbial pathogens. The present review highlights the recent progress in understanding ABA's multifaceted role under stress conditions, particularly stomatal closure. We point out the importance of reactive oxygen species (ROS), reactive carbonyl species (RCS), nitric oxide (NO), and Ca2+ in guard cells as key signaling components during the ABA-mediated short-term plant defense reactions. The rise in ROS, RCS, NO, and intracellular Ca2+ triggered by ABA can promote additional events involved in long-term adaptive measures, including gene expression, accumulation of compatible solutes to protect the cell, hypersensitive response (HR), and programmed cell death (PCD). Several pathogens can counteract and try to reopen stomata. Similarly, pathogens attempt to trigger PCD of host tissue to their benefit. Yet, ABA-induced effects independent of stomatal closure can delay the pathogen spread and infection within leaves. We feel that stomatal closure and other ABA influences can be among the early steps of defense and a crucial component of plants’ innate immunity response. Stomatal guard cells are quite sensitive to environmental stress and are considered good model systems for signal transduction studies. Further research on the ABA-induced stomatal closure mechanism can help us design strategies for plant/crop adaptations to stress.